1999
DOI: 10.1080/135485099106207
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of heterosexual condom use: Characteristics of the situation are more important than characteristics of the individual

Abstract: A bstract An event-speci® c analysis was conducted in order to assess the relative importance of a number of predictors of condom use. Surveys were completed by 271 heterosexual tertiary students: 60% used a condom in their most recent sexual encounter. Condo m use was more closely related to state-like characteristics of the sexual encounter (e.g. having an agreement to use a condo m, use of other form s of contraception) than trait-like characteristics of the individual (e.g. attitudes toward condom use, per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Somlai et al (1998), for example, demonstrated that exist a strong relationship between communication and negotiation skills levels and sexual risk behavior: Individuals with a low level of communication skills had the highest level of sexual risk behavior. Furthermore, De Visser and Smith (1999) showed how important it is for a sexually active couple to be in agreement as a prior step to using a condom; and interpersonal skills are necessary to achieve this collaboration. The interventions that are developed in this field should not only emphasize making young people see the necessity of this behavior, but also provide the abilities and means necessary to allow them to carry it out.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Somlai et al (1998), for example, demonstrated that exist a strong relationship between communication and negotiation skills levels and sexual risk behavior: Individuals with a low level of communication skills had the highest level of sexual risk behavior. Furthermore, De Visser and Smith (1999) showed how important it is for a sexually active couple to be in agreement as a prior step to using a condom; and interpersonal skills are necessary to achieve this collaboration. The interventions that are developed in this field should not only emphasize making young people see the necessity of this behavior, but also provide the abilities and means necessary to allow them to carry it out.…”
Section: Discussionmentioning
confidence: 98%
“…To measure PBC we used two items: ''If I want to use a condom in my sexual relations, I will be capable of convincing the other person to use it, even though he/she uses another contraceptive method'' and ''I consider myself capable of convincing my partner to use a condom every time we have sex.'' The measurement of this construct is based on the selfperception of the subject's persuasiveness, whose importance in STD-preventive behaviors, in general, and regarding condom use behavior in particular, has been highlighted in different studies (e.g., De Visser and Smith 1999;Lo Conte et al 1997;Somlai et al 1998).…”
Section: Variablesmentioning
confidence: 99%
“…First of all, communication and persuasion skills have been identified in several studies as an important factor that requires further attention (e.g., Pulerwitz et al, 2002;Ross, Timpson, Williams, & Bowen, 2003). De Visser and Smith (1999) emphasised how important it is to reach an agreement with the sexual partner as a necessary step to be able to use the condom; and this requires interpersonal skills to achieve the partner's collaboration. The interventions developed in this area should not just try to make young people see the need for this prevention behaviour, but also provide them with the skills and means necessary to carry out the behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Visser and Smith (1999) emphasised how important it is to reach an agreement with the sexual partner as a necessary step to being able to use a condom. When it comes to methodology, correlational research is criticized for being an inappropriate way of analysing causality.…”
Section: Discussionmentioning
confidence: 99%